Oxygen consumption during high intensity exercise - Smith, N. A.; Green, S.; Kerr, G. K. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The VO2 slow component is defined as the slow, continued rise in VO2 during constant load exercise and is only present at workloads above the ventilatory threshold (TVENT). It has been proposed that the VO2 response at high intensities is best described using a biexponential model which, importantly, states that the slow component is delayed relative to the onset of exercise (1). However, the physiological nature of this delayed response remains obscure. To establish that the slow component is delayed, this study modelled the VO2 during exercise below and above TVENT. Four well-trained, male cyclists completed an initial incremental exercise test to determine TVENT. On four subsequent occasions, subjects cycled at 80% TVENT, and following a 30min rest, at TVENT plus 75% of the difference between VO2max and TVENT. The sub-TVENT constant load test always preceded the supra-TVENT and the duration of each constant load test was 8 mins. VO2 was collected on a breath-by-breath basis for each test, interpolated to one value per second, time aligned to the start of the new increment in work, averaged over the four visits, and smoothed with a 5s moving average filter. A monoexponential and two biexponential models were fitted to the data, where the second exponential term either started without (model 1) or with (model 2) a time delay. The biexponential models did not provide a better fit to the sub-TVENT data compared with the monoexponential model; whereas the biexponential models best fit the supra-TVENT data. With respect to supra-TVENT responses, there were no significant differences between models 1 and 2 (p > 0.05) for three of the four subjects, whereas model 2 (with a time delay of 33.7 s) produced a significantly superior (p < 0.05) fit compared to model 1 in only one subject. This subject also demonstrated a unique and consistent reduction (~250mls) in VO2 during the final ~90s of the supra-TVENT exercise bout which may have affected the modelling outcome. This data is in contrast to that of Barstow and Molé (1991) who demonstrated in four subjects model 2 to provide a significantly better fit than model 1. Therefore, our preliminary data suggests that a significant delay in the onset of the VO2 slow component is not a general phenomenon, and that the controlling mechanism(s) of the VO2 slow component can be initiated at the commencement of exercise.